(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2024)
One of the options for reducing cement consumption for the preparation of concrete for bent reinforced concrete structures is the use of two-layer beams with higher strength concrete in the compressed zone and lower strength concrete in the tensile zone, which saves cement without losing structural strength. Experimental tests and theoretical calculations of concrete deformations in the compressed zone of five series of concrete beams with cross-sectional dimensions of b×h = 100×160 mm and a total length of 1500 mm were compared; compressed zone concrete of class C20/25; tensile zone concrete of class C12/15; reinforcement in the tensile zone - 2Ø12 mm of class A400C. The beams differed in the thickness of the concrete layers in the compressed and tensile zones. As a result of the comparison, it was found that the average value of the ratio of theoretical to experimental results was 15.1%; the mathematical expectation of this ratio was 0.856; the coefficient of variation of the ratio was 9.3%, which indicates a fairly high correlation of results.